Guerra de mundos : a estratégia robótica no Twitter durante as eleições presidenciais de 2014 - Regattieri , Lorena Lucas (2017)
Is it possible to speak on a human communication schedule? This dissertation aims to understand the algorithmic role in network in contemporary society, mainly as automated agents - known as robots (bots) - acted on Twitter in the Presidential Elections of Brazil in 2014. We ponder that with the large amount of data (Big data), this reciprocal agency between human and non-human actors is activated through data processing and the mediation in the social media environment. Thus, we consider that the data flux in large quantity is composed in an associative character between human and artificial agents. Our hypothesis is that these actors in relation imply new communication practices and end up transforming public spaces of interaction in social networks (like Twitter and Facebook) creating a culture of massification and notification. Through a qualitative-quantitative method that connects cartography and graph theory, it is possible to collect, analyze and visualize the traces produced by entities of social networks. When dialoguing with theoretical references in philosophy, anthropology, communication, computing and literature, we seek to understand the scale at which the bot as an algorithmic tool changes our way of communicating and the implications in the digital sphere. Our analysis of the 2014 Presidential Elections is based on data collected from Twitter during election debates and the last week of the election. In this way, our discussion problematizes the bot as an algorithmic agent capable of interfering with the way the social is done.